2015
DOI: 10.1371/journal.pone.0126406
|View full text |Cite
|
Sign up to set email alerts
|

The Repellent DEET Potentiates Carbamate Effects via Insect Muscarinic Receptor Interactions: An Alternative Strategy to Control Insect Vector-Borne Diseases

Abstract: Insect vector-borne diseases remain one of the principal causes of human mortality. In addition to conventional measures of insect control, repellents continue to be the mainstay for personal protection. Because of the increasing pyrethroid-resistant mosquito populations, alternative strategies to reconstitute pyrethroid repellency and knock-down effects have been proposed by mixing the repellent DEET (N,N-Diethyl-3-methylbenzamide) with non-pyrethroid insecticide to better control resistant insect vector-born… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
40
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 39 publications
(42 citation statements)
references
References 48 publications
2
40
0
Order By: Relevance
“…These two attributes make it one of the most commonly used insect repellents in the developed world. However DEET has also been shown to dissolve nylons and plastics, blocks human acetylcholinesterase, activates human M3 muscarinic GPCR causing anti-angiogenesis, inhibits mammalian TRPM8, and inhibits mammalian CNGA2 channels, the health consequences of none of which are well understood (Abd-Ella 2015; Corbel 2009; Ditzen 2008; Legeay 2016; Swale 2015). The notion that identification of the mechanisms of action of DEET could help in the development of improved broad-spectrum repellents has resulted in much recent research in this area (Ray 2015).…”
Section: Activation Of Olfactory Receptors Dedicated To Aversionmentioning
confidence: 99%
“…These two attributes make it one of the most commonly used insect repellents in the developed world. However DEET has also been shown to dissolve nylons and plastics, blocks human acetylcholinesterase, activates human M3 muscarinic GPCR causing anti-angiogenesis, inhibits mammalian TRPM8, and inhibits mammalian CNGA2 channels, the health consequences of none of which are well understood (Abd-Ella 2015; Corbel 2009; Ditzen 2008; Legeay 2016; Swale 2015). The notion that identification of the mechanisms of action of DEET could help in the development of improved broad-spectrum repellents has resulted in much recent research in this area (Ray 2015).…”
Section: Activation Of Olfactory Receptors Dedicated To Aversionmentioning
confidence: 99%
“…Other works by Kruse et al 32. on the M2 receptor and the simulation performed by Abd-Ella et al 49. on M1/M3 receptors did support the existence of an allosteric site in human M3 receptor.…”
Section: Discussionmentioning
confidence: 78%
“…Potential mechanisms are inhibition of acetylcholinesterase (AChE)8, modulation of muscarinic receptors49 or the well-conserved ionotropic receptor Ir40a, odorant receptors (OR) and gustatory receptors (GR)75051525354. Among these targets, it has been reported that some inhibitors of human AChE, like donepezil, rivastigmine or galantamine have pro-angiogenic properties in in vitro HUVEC cultured on ECMgel like in chick chorioallantoic membrane and/or in an ischemic hind limb model1455.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To circumvent the problems raised above, the strategy we propose in this review is based on different previous complementary results reporting that (i) insect target sites are strongly regulated by calcium-dependent signalling pathways, (ii) manipulating intracellular regulatory mechanisms of insecticide target sites can have important consequences for the sensitivity of insects towards insecticides, and (iii) insect virus entry into the host cells can produce relatively fast intracellular calcium concentration rise (Thany et al, 2007;Lapied et al, 2009;Lavialle-Defaix et al, 2010;Licznar et al, 2014;List et al, 2014;Abd-Ella et al, 2015). In this case, the insect virus is not used as a bioinsecticide (i.e.…”
Section: Introductionmentioning
confidence: 99%